Advances in Transitional Flow Modeling Applications to Helicopter Rotors - Sheng, Chunhua (SpringerBriefs in Applied Sciences and Technology, 2017)
This book provides a comprehensive description of numerical methods and validation processes for predicting transitional flows based on the Langtry-Menter local correlation-based transition model, integrated with both one-equation Spalart-Allmaras (S-A) and two-equation Shear Stress Transport (SST) turbulence models. A comparative study is presented to combine the respective merits of the two coupling methods in the context of predicting the boundary-layer transition phenomenon from fundamental benchmark flows to realistic helicopter rotors. The book will of interest to industrial practitioners working in aerodynamic design and the analysis of fixed-wing or rotary wing aircraft, while also offering advanced reading material for graduate students in the research areas of Computational Fluid Dynamics (CFD), turbulence modeling and related fields.